1999
DOI: 10.1038/12729
|View full text |Cite
|
Sign up to set email alerts
|

Globozoospermia in mice lacking the casein kinase II α′ catalytic subunit

Abstract: Protein kinase casein kinase II (Ck2) is a cyclic-AMP and calcium-independent serine-threonine kinase that is composed of two catalytic subunits (alpha and alpha') and two regulatory beta-subunits. Ck2 is not a casein kinase in vivo, but over 100 substrates are known. The highly conserved amino acid sequences of its subunits and their broad expression suggest that Ck2 may have a fundamental role in cell function. Ck2 has been implicated in DNA replication, regulation of basal and inducible transcription, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
261
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(272 citation statements)
references
References 24 publications
7
261
1
3
Order By: Relevance
“…PKCK2 is a constitutively active, growth factorindependent serine/threonine protein kinase (40) composed of 2 catalytic ␣ (and/or ␣Ј) subunits and 2 regulatory ␤ subunits (41). Although it is well known that PKCK2 participates in various cellular functions, its biologic activity on chondrocytes has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…PKCK2 is a constitutively active, growth factorindependent serine/threonine protein kinase (40) composed of 2 catalytic ␣ (and/or ␣Ј) subunits and 2 regulatory ␤ subunits (41). Although it is well known that PKCK2 participates in various cellular functions, its biologic activity on chondrocytes has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Ten genes have been found to be associated with globozoospermia, including Csnk2a2 [30], Hrb [3], Gopc [19], Gba2 [31], Zpbp1 [32], Pick1 [11], Vps54 [27], Hsp90b1 [33], Spaca1 [34] and Dpy19l2 [35]. Among 25%.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 CK2a' knockout mice, however, are viable but show profound changes in spermatogenesis. 6 Among the striking number of cellular processes regulated by this protein kinase, a central task of CK2 is the promotion of cell growth and sustenance of cell viability. Indeed, accumulating evidence has demonstrated that CK2 controls critical pathways involved in the triggering of cell proliferation, as well as in the modulation of cell sensitivity to different cytotoxic noxae.…”
mentioning
confidence: 99%